Miconia curvitheca (Melastomataceae), una nueva especie nativa de los bosques altoandinos y subparamos de los Andes centrales, Colombia (2016)
Miconia curvitheca (Melastomataceae) is described and the name is validated. This species is restricted to high Andean forests and subparamos and is distributed in the southern and central part of the Central Colombian Cordillera of the Andes between 2900 and 3700 m elevation from the department of Cauca to the limits of the departments of Quindío, Tolima and Valle del Cauca. It is characterized by the curved shape of its anthers and differs from the most similar species, M. cuatrecasae, by the following combination of characters: smaller leaves, always bisexual flowers and ovary always four-celled.